On the Model of Transport of Salt Solution in a Xylem - Evgeny Leonidovich Pankratov, (Indian Journal of Advanced Mathematics (IJAM), 2025)
We consider a model for vertical lifting of an aqueous solution of salts in a xylem. We analyzed changes of movement of the considered solution depending on various parameters. We consider an analytical approach for analysis of the considered model. The approach gives a possibility to take into account changes of parameters in space and time, as well as the nonlinearity of the considered processes.